Real‐life activity of eribulin mesylate among metastatic breast cancer patients in the multicenter national observational ESME program. Issue 12 (20th June 2019) - Jacot, William; Heudel, Pierre‐Etienne; Fraisse, Julien; Gourgou, Sophie; Guiu, Séverine; Dalenc, Florence; Pistilli, Barbara; Campone, Mario; Levy, Christelle; Debled, Marc; Leheurteur, Marianne; Chaix, Marie; et al.
Abstract : Eribulin mesylate (EM) was recently approved for metastatic breast cancer (MBC) chemotherapy (CT) in late lines by the FDA, with debated results in second line. We evaluated outcomes in breast cancer patients receiving EM as second, third and fourth line in a national real‐life cohort of 16, 703 consecutive MBC patients initiating their first metastatic therapeutic line between 2008 and 2014. Primary and secondary objectives were overall survival (OS) and progression‐free survival (PFS). An imbalance was seen for HER2+ tumors and concomitant anti‐HER2 targeted therapies use, we thus performed a subanalysis in HER2− patients. PFS and OS were significantly better in EM patients in third and fourth lines, compared to "Other chemotherapies" patients (PFS: 4.14 vs . 3.02 months, p = 0.0010; 3.61 vs . 2.53 months, p = 0.0102, third and fourth‐line; OS: 11.27 vs . 7.65 months, p = 0.0001; 10.91 vs . 5.95 months, p < 0.0001, third and fourth‐line). No significant difference was reported in second‐line (PFS: 5.06 vs . 4.14 months, p = 0.1171; OS: 13.99 vs . 11.66 months, p = 0.151). Among HER2− patients, a significant difference was seen for all lines, including 2nd‐line (PFS: 4.57 vs . 3.91 months, p = 0.0379; OS: 14.98 vs . 10.51 months, p = 0.0113). In this large real‐world database, HER2‐negative MBC patients receiving EM in second or later CT line presented significantly better PFS and OS. This difference disappeared in second line in the overall population, probably because of the imbalance in HER2‐targeted treatments use. Our results mirror those of the published randomized trials. The effect of anti‐HER2 therapies addition in this setting still needs to be defined. Abstract : What's new? An emerging therapy for metastatic breast cancer may extend survival over other chemotherapies. Eribulin mesylate (EM), a microtubule‐dynamics inhibitor, was approved by the FDA in 2010 as a later‐line therapy for metastatic breast cancer. Here, the authors evaluated EM effectiveness by analyzing data from 16, 703 MBC patients. Treatment with EM as a third or fourth line therapy improved survival compared to other chemotherapy, but as a second line therapy, EM only benefited patients with HER2‐ disease. Since this trial was retrospective, not randomized, different proportions of patients in the two treatment groups received HER‐targeting therapies, which may have influenced the result.